Enzymatic Cocktail Formulation for Xylan Hydrolysis into Xylose and Xylooligosaccharides - Bueno, Danilo [UNESP]; de Freitas, Caroline [UNESP]; Brienzo, Michel [UNESP] (MDPI, 2023)
In the context of a biorefinery, lignocellulosic materials represent an important source of raw material for the bioconversion of cellulose, hemicellulose, and lignin into value-added products, such as xylose for fermentation, oligosaccharides, and bioplastics for packaging. Among the most abundant lignocellulosic materials in Brazil, sugarcane bagasse biomass stands out, as it is rich in cellulose and hemicellulose. In this context, through an experimental design, this study developed a robust enzyme cocktail containing xylanases and accessory enzymes to complete the hydrolysis of xylan from sugarcane bagasse, obtaining a low xylose yield and concentration (9% and 1.8 g/L, respectively, observed in experiment number 16 from the complete hydrolysis of a xylan assay), a fermentable sugar that is important in the production of second-generation ethanol, and a high xylooligosaccharides (XOS) yield and concentration (93.1% and 19.6 g/L, respectively, obtained from a xylooligosaccharides production assay); in general, xylan has prebiotic activities that favor an improvement in intestinal functions, with immunological and antimicrobial actions and other benefits to human health. In addition to completely hydrolyzing the sugarcane bagasse xylan, this enzymatic cocktail has great potential to be applied in other sources of lignocellulosic biomass for the conversion of xylan into xylose and XOS due to its enzymes content, involving both main chain and pendant groups hydrolysis of hemicelluloses.
Keywords: bioactive compounds; biomass conversion; biorefinery; enzymatic hydrolysis; high-added-value products